1981
DOI: 10.1002/pol.1981.170190227
|View full text |Cite
|
Sign up to set email alerts
|

Redox cationic polymerization: The diaryliodonium salt/ascorbate redox couple

Abstract: Diaryliodonium salts undergo facile copper catalyzed reduction in the presence of Sn(I1) compounds. Such redox couples can be employed for the in situ generation of active initiators for cationic vinyl and ring opening polymerizations. Two mechanisms are proposed for the reduction reaction to explain the stoichiometry of the reactants and nature of the products formed. The polymerizations of several representative cationically polymerizable monomers were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Indeed, much of the reaction chemistry of both these classes of compounds involves their reduction. Work in this laboratory has shown that diaryliodonium salts can be employed together with reducing agents such as ascorbates [9], benzoins [10] , or tin(II) compounds [11] to initiate cationic polymerizations at room temperature , . Similarly, oxidizable free radicals generated either by thermolytic or by photolytic methods can be used as reducing agents for diaryliodonium salts.…”
Section: I Imentioning
confidence: 99%
“…Indeed, much of the reaction chemistry of both these classes of compounds involves their reduction. Work in this laboratory has shown that diaryliodonium salts can be employed together with reducing agents such as ascorbates [9], benzoins [10] , or tin(II) compounds [11] to initiate cationic polymerizations at room temperature , . Similarly, oxidizable free radicals generated either by thermolytic or by photolytic methods can be used as reducing agents for diaryliodonium salts.…”
Section: I Imentioning
confidence: 99%
“…It is known that the DPI路BF 4 /BPO initiator system makes the reaction to form a free radical-cationic dual reaction system, in which the free radical produced from BPO can accelerate cationic ring-opening reaction and plays a coordination role for cationic reaction, because it plays an indirect role in the electron transfer of the iodonium salt [13][14][15]. The free radical is produced through the thermal decomposition of BPO at about 80 掳C , which could act as the reducing agent of onium salts, and induce DPI路BF 4 to generate cationic active state.…”
Section: The Effect Of Bpo Content On Thermal Polymerizationmentioning
confidence: 99%
“…But the report for the thermal cationic polymerization initiated with phenyliodonium salt is fewer than others. The thermal cationic polymerizations of cyclohexene oxide, tetrahydrofuran, and s-trioxane using the diaryliodonium salt/ascorbate redox couple as initiator were studied by Crivello et al [15]. We have already studied the hybrid free radical-cationic thermal polymerization of methylacryloylpropyl-POSS/epoxy resin nanocomposites [16].…”
Section: Introductionmentioning
confidence: 97%
“…Crivello et al found that the diaryl iodonium PAG is reduced during the decomposition reaction, and the products can lower the energy required for the deprotection reaction. 16 It is likely that TMPEO acts as a reducing agent in this system, and the decomposition temperature of the PAG depends on the concentration of TMPEO. The QCM and TGA results correlate well for formulations with 3 pphr PAG and 10 pphr TMPEO.…”
Section: Methodsmentioning
confidence: 99%